THE IMPROVEMENT OF COGNITIVE QUALITIES THROUGH PLAY - Scientific supervisor: Fayzullayeva Dilnoza Student: Marufova Eldona Student of (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article explores the idea that playing video games can improve cognitive qualities such as critical thinking, problem-solving skills, and strategic planning. The article highlights the benefits of approaching learning tasks like a video game, breaking them down into smaller challenges to stay motivated and engaged. It concludes that video games can be a powerful tool for learning and personal growth, improving cognitive qualities that can benefit individuals in various aspects of their lives.